Magnetic Resonance Imaging Signal Alterations in Paraspinal Muscles in Dogs with Acute Thoracolumbar Intervertebral Disk Extrusion - Trampus, Peter; Goepfert, Christine; Welle, Monika; Henke, Diana; Forterre, Franck; Schweizer-Gorgas, Daniela (Frontiers in Veterinary Science, 2018)
Muscle signal alteration detected on MRI is seen in diverse pathologic conditions. We observed signal alterations within the paraspinal muscles in dogs with acute thoracolumbar intervertebral disk extrusion. The aim of this retrospective study was to describe MRI features of paraspinal muscle signal alteration in dogs with acute thoracolumbar intervertebral disk extrusion and to investigate an association of the signal alterations (SI) with neurological grade, type and location of intervertebral disk extrusion, degree of spinal cord compression and presence of epidural hemorrhage. Medical records of dogs undergoing MRI because of thoracolumbar intervertebral disk extrusion between August 2014 and June 2016 were reviewed. MRI was evaluated for SI changes within the paravertebral musculature, their location, extension, affected muscles, contrast enhancement and signal void in T2* sequences. Intervertebral disk herniation was categorized as acute non-compressive nucleus pulposus extrusion (ANNPE) or compressive intervertebral disk disease. In five patients, muscle biopsies of areas with SI changes were taken during surgery. In total, 103 dogs were enrolled in the study. Paraspinal muscle signal alterations were visible in 37 dogs (36%) affecting the epaxial muscles (n = 17), hypaxial musculature (n = 12), or both (n = 8). All signal alterations were hyperintense on fat-suppressed T2-weighted images and iso- or hypointense in T1-weighted images. Signal void in T2* was not observed in any dogs. Postcontrast sequences were available in 30 of the 37 dogs and showed enhancement in 45%. There was neither an association with degree of compression nor epidural hemorrhage. Intervertebral disk extrusion caudal to L1 and a higher neurological grade was associated with the presence of muscle changes. Histopathology revealed mild to moderate acute muscle fiber degeneration with edema and necrosis in 3 of 5 samples. The MRI, as well as the muscle samples, show rather unspecific changes. The underlying pathomechanism might be related to ischemia or muscle spasm, but also denervation edema may explain the signal alteration.